The process of school integration of immigrant pupils in primary school - Rodríguez Navarro, Henar; García Monge, Alfonso; Retortillo Osuna, Alvaro (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
The following article analyzes the exclusion in an environment composed of different groups of students (gypsy and immigrants). The text, broken into two parts, first shows sociometric results and existing prejudice within a sample of 539 fifth grade students. Then, using school ethnography, some explanatory factors for school exclusion are highlighted. Finally we have developed some specific indicators that help educators detect marginalization within the school context
Keywords: Ethnic exclusion; School integration; Social minorities; Social interactions between peers; School exclusion indicators